The relationship between project management and e-collaboration - Mohammad Jafari, M.; Ahmed, S.; Md Dawal, S.Z. (2010)
Understanding and enhancing the value of electronic collaboration (E-collaboration) technologies is essential for supporting distributed projects. Development of E-collaboration has provided workable infrastructures for group communication and information processing. Also E-collaboration has the potential of networking and collaborative technologies to support the project management teams in the creation of shared understanding. On the other hand, project management has been considered as an academic field for planning, organizing, controlling to producing products with predictable cost, time and quality and, in other applications of engineering requirements. A conceptual relationship between project management and E-collaboration can play a vital role in addressing many problems among the participating companies. In this paper we review the relationship between E-collaboration and project management in industry. And it is going to present some definitions such as E-collaboration, its evolution, past research on E-collaboration, and project management, and the need of it to project management based on conceptual model. A guide line for future research is also presented.